Skateboarder, trade mola - Unidentified artist (Colorado State University. Libraries, 1990)
Identified as a skateboarder by a tourist.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, yellow, blue); reverse and direct appliqué.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama